Genetic and environmental factors as strong determinants of atopic allergic disease clinical manifestations in surabaya's school children - Soegiarto, Gatot; Damayanti, Luki Agustina; Effendi, Chairul (Folia Medica Indonesiana, 2017)
This case-control study was conducted to assess the relative role of genetic and environmental factors in determining the clinical manifestations of atopy allergy disease in school children, which is part of a large study of the prevalence of allergic diseases in school children in Surabaya. Using a simple multi-stage random sampling, 348 children from 5 elementary schools, 4 junior high schools, and 4 senior high schools in Surabaya were involved in the study. The subjects of the study along with her parents were guided to fill out the modified ISAAC questionnaire and underwent physical examination and skin prick test using 27 common allergen types found in the environment. For the analysis, 110 school children were randomly selected from the parent sample and included in the case group of 55 people (positive skin prick test against > 1 type of allergen), and the control group of 55 people (negative skin prick test). All genetic and environmental factors data were collected and analyzed. Most of the subjects had clinical manifestations of allergic rhinitis (66.36%), asthma (21.82%), food allergies (10.9%), and atopic dermatitis (6.36%). Complete models for multiple logistic regression analysis can only be performed for overall atopic disease and allergic rhinitis disease. The first birth order and exposure to home dust mites were the most significant clinical manifestations of atopy disease (OR 4.548, 95% CI: 1.813-11.410, p=0.01). Atopy status of the father was the only significant determinant factor for the manifestation of allergic rhinitis in the study subjects (OR 3.929; 95% CI: 1.143-13.052, p=0.03). Both genetic and environmental factors interacted and determined clinical manifestations of atopy allergy disease in school pupils. The father's genetic factors were more dominant than maternal genetic factors in determining the clinical manifestations of allergic rhinitis in offspring.